Energy efficiency and emission flexibility: Management and economic insights for renewable energy integration - Abid Hussain; Alida Huseynova; Yegana Hakimova; Abdelmohsen A. Nassani; Bai Bo (Energy Strategy Reviews)
This study suggests a multi-regional power system optimization model to evaluate the impact of various flexibility options on reducing carbon emissions in the Chinese power sector. This model considers factors such as total carbon emissions, peaking timetables and values, carbon emission transfer between regional power systems, and changes in carbon emission sources between technologies. The findings reveal four primary outcomes: first, renewable energy integration significantly improves energy efficiency across all G7 nations, although the degree of impact varies among them. Second, emission flexibility mechanisms, such as carbon trading and adaptable regulatory policies, have positively influenced emission reductions without compromising economic growth. Third, the interaction between energy efficiency and renewable energy use is shown to be mutually reinforcing, particularly in the countries with high levels of technological innovation. Fourth, energy policy frameworks that adapt to fluctuating grid demands and environmental targets have a measurable effect on reducing greenhouse gas emissions. The results suggest that policy efforts should focus on enhancing adaptive regulatory frameworks and investment in renewable technologies, which are crucial for achieving long-term emission reduction goals while maintaining economic resilience in the G7.